PENINGKATAN PERAN GENDER DALAM PENGELOLAAN HUTAN RAKYAT DI KONAWE SELATAN, PROVINSI SULAWESI TENGGARA - Nurhaedah Muin; Achmad Rizal Hak Bisjoe; Bugi Kabul Sumirat; Wahyudi Isnan (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2019)
National strategy on gender that stated in Presidential Instruction No. 9/2009, was also applied in private forest management. The composition of private forests which generally consist of woody plants, agricultural crops, and lower crops, allows for the sharing of gender roles in their management, as found in South Konawe. Research methods used survey method and interviews through Focus Group Discussion (FGD). Data were analyzed qualitatively and quantitatively. The results of the study indicate that there is a share-out of roles between men and women in private forest management in South Konawe. Men play a dominant role in the management of woody plants, starting from planting to logging while women are dominantly involved in the lower crop cultivation. Women’s involvement have greatly helped the family economy through selling vegetables and sago for family consumption as well as to meet daily needs. Supporting activities in private forest management such as attending farmer group meetings and being administrators of farmer groups are still dominated by men. For this reason, it is necessary to consider the proportional involvement of women in private forest management so that they can contribute more to the family needs.